Affect and Effect of Overpainting at the Age of Neo-muralism - Tremblin, Mathieu (Street Art & Urban Creativity, 2024)
The art historical term pentimento is used to indicate areas in painting that have been modified or overpainted by the artist during the creative process. The process of tagging, covering and erasing existing graffiti and street art murals transforms the original visual work. When not restored, these ‘agonist ornaments’ generate an in-between graphic status to the mural, highlighting an ongoing conversation at the scale of the city. This dialogic aspect invites us to consider the shape of urban landscape as collective responsibility. Each overpainting transformation can thereby be considered to have the possibility of revealing affect and effect related to hidden power dynamics. Considering the walls of the city as a palimpsest, the author analyses a series of murals through the lens of overpainting dynamics and offers an updated and site-specific understanding of the concept, combined with urban core topics such as social control tendencies, game as urban approach, and expression of emotions in public space. The author concludes that the upcoming processual beauty of contemporary muralism can be attributed to a chain of interactions where various actors depends one each other, the ‘pentimento’ of the collective author.